VARIATIONS IN THE AGE OF FUSION OF ISCHIAL TUBEROSITY; A RADIOLOGICAL STUDY - Siddiqi, Hina; Nisar, Sarah; Waheed, Nazish (Journal of Ayub Medical College Abbottabad, 2017)
Background: Human skeleton develops from separate ossification centres which continue to ossify till the bone is completely formed. Radiological techniques are very reliable and useful method for estimating the age of individual for forensic and criminal reasons by observing these ossification centres. External inspection for age determination is liable to error. This study is thus aimed to assess the variation in age of fusion of ischial tuberosity in Pakistani population. Methods: It was a cross sectional study, wherein data was retrospectively collected at Bahawalpur Victoria Hospital, a tertiary referral centre in which consecutively selected 47 females and 121 males between 10 to 24 years of age, attending the outpatient, referred from National Database and Registration Authority for the confirmation of age were selected. Results: There were a total of 13 cases in stage I, 98 in stage II, 23 in stage III and 34 in stage IV. In stage II maximum numbers of cases were between the ages of 19-22 years whereas in stage IV the maximum numbers of cases were between 21-24 years of age. Conclusion: It is concluded that the earliest appearance of epiphyseal center in males occurred at 12-13 years and in females at 10-11 years. While earliest complete union was seen at the age of 19-20 years in females and 16-17 years in males. All cases in age group of 23-24 years showed complete union. Keywords: Epiphysis; Ischial tuberosity; Ossification centres; Age determination